Formulation Of Beetroot Cookies With Addition Of Iron (Fe) As Alternative Food Prevention Of Anemia - Gita Suryani; Avliya Quratul Marjan; Iin Fatmawati (Universitas Islam Negeri Walisongo Semarang, 2019)
The purpose of this research was to analyze the difference of formulation with the substitution of bit flour and the addition of Fe to the organoleptic properties, chemical properties and physical properties in the manufacture of cookies as alternative food for the prevention of female anemia. This research was conducted by experimental method with Completely Randomized Design. The results of this study showed that the first organoleptic test of cookies with 15% beet meal substitution and 30% fortified cookies was the selected formula. Selected formula cookies have higher water content, ash content, protein content, carbohydrate levels and higher Fe content compared to control cookies, whereas the selected fatty acid formula content is smaller. The Fe content in selected cookies belongs to the food of the Fe source snack. Selected formula cookies are redder and darker than the control formula cookies. The contribution of iron to nutrition label reference in cookies is 26%.